Effect of Teacher Attrition on Academic Performance of Students in Uasin Gishu County, Kenya - Sr. Mary Theodora Mabeya; Margaret Gikuhi; Ntabo Jared Anyona (IJRDO- Journal of Educational Research, 2019)
The study was on the effect of teacher attrition on students’ academic performance in public secondary schools of Uasin- Gishu County, Kenya. The study employed a mixed research design, which included naturalistic and descriptive survey designs. The target population comprised all public secondary school teachers in Uasin-Gishu County, County Education officials, teachers who had left teaching and form 3 and 4 students. Data collection instruments included Questionnaires for teachers and students, interview schedule for County Education officials and document analysis guides. Analysis of data has been through use of descriptive and inferential statistics. The study revealed that there existed a positive correlation between teacher attrition and students’ academic performance, which was statistically significant. It was also established that attrition has a negative effect on students’ academic achievement as it increases teachers’ workload, shortages, curriculum implementation, creates poor image on teaching as a profession and denies students’ future career. . The study therefore recommended that the Ministry of Education and the Teachers’ Service commission should employ more teachers. The school principals should therefore make fair decisions and promote open discussions when dealing with teacher issues in order to use the feedback from teachers to improve any strained relationship.